Berkumur Air Rebusan Jahe Merah (Z.Officinale Var Rubrum) Terhadap Perubahan Potential of Hydrogen (pH) Saliva Rongga Mulut - Sitanaya, Rini; Irayani Yunus, Surya; Septa , Badai; Hapsari (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Gargling with mouthwash can remove bacteria between teeth that are not reached by a toothbrush. The mechanism of action of mouthwash is to clean the oral cavity thoroughly, namely mechanically and chemically. Long-term use of chemical antiseptic mouthwash can cause changes in salivary pH. This experiment was conducted to determine the effect of red ginger boiled water (Z.Officinale var rubrum) on salivary acidity or salivary pH of the oral cavity. The type of research used is quasi experimental research, which is experimental research carried out in only one group called the experimental group without a comparison group or control group. Changes in salivary pH were measured before and after gargling with red ginger boiled water. Red ginger water decoction is proven to increase the pH value of saliva and also has the ability to inhibit bacterial growth so as to maintain the acidity of the oral cavity. Conclusion: There is an increase in salivary pH after gargling with red ginger boiled water.